Asset Return in Money Laundering - Boong, Vicariya Retnowati; Irawan, Joshua Evandeo; Ibrahim, Christian; Jonathan, Steven (Faculty of Law, Universitas Lampung, 2023)
Money Laundering Crime as a further criminal act has placed and involved two main perpetrators, namely active actors as parties trying to hide or disguise the origin of assets that are the result of criminal acts in various ways, and passive actors as parties who receive Money Laundering Crime assets. The return of Money Laundering Crime assets is not only through coercive measures, but also requires a voluntary return by the receiving party. In practice, voluntary returns create uncertainty when the receiving party (passive actor) from the beginning does not know the origin of the assets received. Through various money laundering cases in Indonesia in June-July 2022, the Authors are very interested in analyzing the extent of obligations related to the return of Money Laundering Crime assets. This research uses normative juridical methodology with Law approach and concept approach. The purpose of this study is to determine the obligations that must be carried out by passive trafficking actors based on Law No. 8 of 2010.